Performance Evaluation of a No-Husk Corn Sheller: A Case Study at Benteng Tellue Workshop - Ramadhan, Syahrul; Muhammad Tahir Sapsal; Junaedi Muhidong (Salaga Journal, 2024)
The post-harvest handling of corn involves threshing, the process of separating kernels from the cob. A corn shelling machine without husking offers advantages for both sellers and buyers by allowing manual sorting of good and damaged kernels before threshing. This study evaluates the performance of a no-husk corn sheller used in the Amali District, Bone Regency. Key parameters analyzed include fuel consumption, shelling capacity, percentage of damaged kernels, and cleanliness level at three different rotational speeds (500, 600, and 700 rpm). The results indicate that increasing the rotational speed leads to higher fuel consumption and improved shelling capacity. However, the percentage of damaged kernels decreases with higher speeds, achieving an average damage rate of 0.049%. Additionally, the cleanliness level of the shelled corn reaches an average of 98%, confirming the machine’s efficiency. These findings suggest that optimizing the rotational speed enhances both productivity and output quality, making the no-husk corn sheller a viable tool for post-harvest processing.